The role of Vesiculararbuscular mycorrhizal (VAM) fungi in alley cropping - Fagbola, O.; Awotoye, O.O.; Atayese, M.O.; Osonubi, O.; Mulongoy , K. (1995)
Alley cropping trials were conducted on different parts (top, middle and base) of a sloping land to compare the effects of inoculation with vesicular-arbuscular mycorrhizal (VAM) fungi on Senna siamea, Gliricidia sepium and Leucaena leucocephala and cassava (Manihot esculenta Crantz) intercrop on an Alfisol in subhumid southwestern Nigeria. The above ground biomass yield of hedgerow trees one year after establishment was higher at the base than at the top of the slope, bur was not influenced by VAM inoculation at the top of base of the slope. At the middle of the slope, VAM inoculation significantly increased leaf biomass of the hedgerows without influencing their stem biomass. The root yield of alley-cropped cassava at the top and middle of the slope was not affected by VAM Inoculation. Inoculation significantly increased the P and N uptake of the hedgerows in all treatments, and fresh tuber yield of cassava only at the base of the slope.